Persepsi Masyarakat terhadap Pengaruh Bumdes dalam Pengembangan Ekonomi Masyarakat di Desa Tebing Tinggi Kecamatan Benai - Haris Susanto; Mashadi Mashadi; Melisasmi Melisasmi; Gusti Marlina; Mahrani Mahrani; Finu Audian A; Berli Eka Pratama (SENTRI: Jurnal Riset Ilmiah, 2025)
The research objectives to be achieved are to: Analyze the Influence of Village-Owned Enterprises on Community Economic Development in Tebing Village, Benai District, Kuantan Singingi Regency and Identify community perceptions of the influence of Harapan Makmur Village-Owned Enterprises (BUMDes) in community economic development in Tebing Tinggi Village, Benai District, Kuantan Singingi Regency. Data was collected directly at the research location through observation and interviews with Ms. Melisasmi, the manager of a village-owned enterprise (BUMDes) in Tebing Tinggi Village, Benai District. The required sample size was calculated using the Slovin formula. A total of 94 respondents were selected. Based on the results of research that has been conducted on public perception of the influence of BUMDes in the development of the community's economy in Tebing Tinggi Village, Benai District, Kuantan Singingi Regency, where the total score is 251.27% with an average score of 83.76%. Community economic development through BUMDes is the highest score result compared to the other 3 variables that influence public perception of the influence of BUMDes in community economic development, namely with an average score of 88.24%. This shows that community economic development through BUMDes is something that has a very large influence on the development of the community's economy towards the existence of BUMDes. While internal factors are the lowest average score results compared to the other 3 variables that influence public perception of the influence of BUMDes Harapan Makmur, which is only 80.05%. While for external variables with an average score of 82.94%.